Applying Model Driven Approach for Gamification of Educational Courses: Action Research - Seyedeh Hasti Mousavi; Shekoufeh Kolahdouz-Rahimi; Leila Samimi-Dehkordi (Vesnu Publications, 2020)
Introduction: The importance of education in today's world is evident for anyone. Nowadays, with the advancement of technology, educational centers seek electronic approaches to train the students. On the other hand, education authorities encounter difficulties like abundant educational material, limited learning time, lack of interactive media, and poor quality of education that negatively influence student's motivation and engagement. An effective solution in this regard is gamification in the electronic learning. Additionally, software developers encounter many complexities in producing courses that use game elements for learning, including lack of precise understanding of the concepts of the field, which makes the development of the software a time-consuming process. Materials and Methods: In this study, the process of designing and implementing courses was simplified for developers by modeling the concepts of gamification using the model driven approach. A metamodel was designed for e-learning domain using Eclipse framework, and then a model was has developed based on this metamodel that represented a gamification course. Results: A meta-model was created for modeling gamification of electronic education using a model driven approach and then a model was developed based on this metamodel that indicated a gamification course for educational purposes. Conclusion: In this study, the learning process becames more attractive by applying gamification, in addition to facilitating e-course development process, which was usually implemented in web platforms using the model driven approach. Different models may be specified conforming to the metamodel presented in this study according to the requirements of customers. These models may be used in transformation programs to generate implementation code for e-courses.